Study guide : HBEC2503: Mathematics in early childhood education - Badzis, Mastura; Yang, Norzaini (Open University Malaysai (OUM), 2012)
This course is based upon the study of children as they emerge as mathematical thinkers. While revisiting some of their mathematical concepts, early childhood educators will gain firs- hand knowledge of the concepts and processes involved in working with a community of early mathematical learners. Students will be challenged to work with mathematics at their own level and at the same time relate the process of learning and teaching to the young child’s context. By exploring ways to become creative problem solvers, students will develop their own mathematics and gain insight into the learning and teaching of mathematics in the early years. This course helps early childhood educators explore early childhood mathematics in-depth and understand what children already know about mathematics, how they think about it and how they learn it.